Semen characteristics and hormonal profile of Yankasa rams fed a mixed ration of cowpea husk (Vigna unguiculata L. Walp) and tiger nuts (Cyperus esculentum L.) residue - Njidda, Ahmed Amin; Butswat, Isaac Sammani; Yakubu, Hosea; Chibuogwu, Ijeoma Chika; Bankole, Abayomi Samuel (Brazilian Journal of Science, 2024)
Thirty growing and healthy Yankasa rams were randomly allotted five dietary treatments with six animals per treatment to ascertain the effect of diet on their reproductive potential and hormonal profile. Treatments compared were T1 (cowpea husk 40% + tiger nuts residue 0%), T2 (cowpea husk 30% + tiger nuts residue 10%), T3 (cowpea husk 20% + tiger nuts residue 20%), T4 (cowpea husk 10% + tiger nuts residue 30%), and T5 (cowpea husk 0% + tiger nuts residue 40%). The results of the chemical composition of the diets showed that the dry matter was high for all treatments. The semen characteristics and hormonal profile showed significant differences (p < 0.05) in all the parameters observed but were within normal ranges. However, the group fed a high percent tiger nut mixed ratio had a depreciating effect on semen characteristics, and LH, FSH, and testosterone levels. There is no deleterious effect on the reproductive potential of growing Yankasa rams fed varying levels of cowpea husk and tiger nut residue at the inclusion levels in this study. Hence, it is safe to feed breeding rams the ration mix. However, the authors advise caution of including tiger nuts levels of up to 40% in a mixed ration. further investigation may be conducted with ewes to determine the effect of a mixed ration of cowpea husk and tiger nut residue in reproduction.